Looking north up the Dyea River south of Canyon City, Chilkoot Trail, August 28, 1897 - University of Washington Libraries. Special Collections Division. (1897)
This shot is looking north up the Taiya River Valley, from about where the Nourse and the Taiya (Dyea) Rivers converge. To the west (left) is the Nourse valley and to the east (right) is the Upper Taiya valley, through which the Chilkoot trail runs. The mountain directly in view is Mount Hoffman, and the Glacier to the right is the Saussure Glacier, so named since 1883. This entire valley was considered the Dyea Valley, Dyea Canyon is about a mile or so up river to the east (right). PH Coll 35.444